(3SDGd hLhGH aj HjY GdKeQI bHd HOA UdGMgGs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3SFd GdYdGeI TjN GdESdGe Hf JjejI GdMQGfi QVi Gddg Yfg Yf VeGf GdHSGJjf hGdCQV GdJi ajgG GdfNjd hGdTLQ ZjQ GdfNjd bHd Cf jHOA UdGMg hgd jLhR VeGf GdSfI hGdSfJjf s
(3BNQgG (B:s
(3haQW MJi JdaJ GdYjf ChGNQ Pdc dWdH aEf GdVeGf gfG jchf ef eGdg hGddg SHMGfg hJYGdi CYde Je GdLhGH GdeHGQc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bhHdJ hUMMJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdMfHdjs